Visualization of fluid simulation: An SPH‐based multi‐resolution method. (25th May 2018) - Zhang, Guijuan; Lu, Dianjie; Liu, Hong
Summary: Fluid simulation is an important research topic since it is widely used in virtual training, education, computer games, and digital entertainment. Generating fluid simulation results with high degree of visual realism is challenging in these applications. We present a visualization approach for fluid simulation in this paper. Our method allows students to understand the complex natural phenomena so as to solve the fluid engineering problems intuitively. In this study, an SPH (Smoothed Particle Hydrodynamics)‐based multi‐resolution method is proposed for fluid simulation. The method can keep the accuracy while improve the efficiency significantly. We construct a multi‐resolution fluid model from bottom to top by combining fluid computation and surface reconstruction. We first compute multi‐resolution particles with a novel adaptive SPH model in the bottom layer. Next, surface particles are extracted and pre‐processed to provide samples for surface extraction. Then, the multi‐resolution surface reconstruction model is built in the top layer. Meshes from different reconstruction resolutions are merged to obtain the final fluid surface. Experimental results show that our approach can effectively represent multi‐scale fluid details and efficiently produce visual‐pleasing fluid simulation results.